Persetujuan Tindakan Medis (Informed Consent) - Matippanna, Ampera (Jurnal Pro Hukum : Jurnal Penelitian Bidang Hukum Universitas Gresik, 2022)
This study aims to determine the approval of medical treatment including legal basis, procedure, form and type, legal requirements, elements, function, purpose and impact. This study uses qualitative research methods, while the data collection techniques are carried out by exploring journals, books and other information relevant to the study. The results of the study show that the legal basis is strictly regulated in positive laws that apply in Indonesia, including the Medical Law, Hospital Law, Health Law and Health Personnel Law. Then, therapeutic communication procedures in giving consent for action and there is sufficient understanding from the patient or his family regarding the medical action to be carried out along with all possible risks that may occur. Meanwhile, in the form and type, the agreement is divided into two, namely tacit approval and clear approval. The legal requirement for approval of medical action is a unilateral legal act carried out by the patient or his family, but the conditions for its implementation require the involvement of a doctor or the hospital. The elements consist of elements of medical information, elements of providing medical information and elements of giving consent for action. This approval for medical action is held to function as a law that regulates the behavior of doctors and patients in carrying out medical actions. While the purpose is for the benefit of medical action, law, medical ethics and the interests of the administration of health services. The implementation of informed consent in accordance with the procedures and provisions of applicable laws and regulations will have a broad impact on the health care system, especially in the implementation of medical practice where the patient's right to obtain medical information and self-determination is highly respected, so as to prevent the occurrence of malpractice cases.